The Use of Metaphors, Similes, and Personifications in the Truman Show Film - Pamungkas, Adjie; Yuskar, Bobby Octavia; Miftahulkhairah Anwar; Zuriyati (CV. Creative Tugu Pena, 2024)
This research dissects “The Truman Show” using metaphor, simile, and personification to expose concealed symbolism. The study employs a qualitative method, scrutinizing the film’s script based on X.J. Kennedy’s theory. Data is gathered through film observation and noting the usage of these literary devices. The film primarily uses personification (41.2%), followed by metaphor (35.3%) and simile (23.5%). These devices stimulate viewers to question reality and the media’s impact. They underscore the significance of privacy in genuine life experiences. The film serves as a warning, revealing how turning real life into entertainment can dehumanize individuals and reminding us of the value of privacy as a crucial part of a genuine life experience. The study follows a systematic process, including outlining the topic, creating the thesis layout, gathering information from the film and online research, and analyzing the symbols and meanings in the thesis. The research provides insights into human experiences and the impact of media on our perception of reality. Keywords: The Truman Show, Concealed Symbolism, Metaphors, Similes, and Personifications